Unlocking Learner Potential: Assessment as a Tool for Understanding Learning Styles in the Merdeka Curriculum - Al Bashir, Muhammad Nizar; Siti Fatonah (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2025)
This research delves into the multifaceted realm of student learning styleswithin the assessment framework of the Merdeka Curriculum. Employing aqualitative approach through an extensive review of academic literature, itmeticulously examines a vast array of scholarly journals and books to unravela comprehensive understanding of learning styles and their profoundimplications for assessment practices. The meticulous analysis unveils threeprominent categories of learning styles: visual, auditory, and kinesthetic. Thesestyles are not merely static traits but rather dynamic constructs shaped by acomplex interplay of internal factors, such as individual personalitycharacteristics, and external influences, including the ever-evolving modernera. As a result, many contemporary students exhibit a combination of learningstyles, defying rigid categorization into a single style. The MerdekaCurriculum, with its inherent flexibility, empowers educators to embark on ajourney of mapping the diverse learning styles of their students. This valuableinformation is then strategically transformed into a powerful tool for designingassessments that resonate with the unique strengths and preferences of eachlearner. By tailoring assessments to align with a student's preferred learningstyle, educators can foster a more inclusive and supportive learningenvironment, ultimately propelling each student towards achieving thedesignated learning objectives. This research serves as a valuable contributionto the evolving landscape of understanding learner styles and their profoundimplications for assessment practices in the era of the Merdeka Curriculum. Byrecognizing the multifaceted nature of learning styles and the importance ofcatering to learner diversity, educators can embark on a transformative journeytowards designing assessments that empower each student to reach their fullpotential and achieve the desired learning outcomes.